2012
DOI: 10.2139/ssrn.2207625
|View full text |Cite
|
Sign up to set email alerts
|

CDS Spreads and Systemic Risk - A Spatial Econometric Approach

Abstract: In the current crisis, credit risk not only evolved from a financial institution's fundamentals but also from a system-inherent mechanism of risk propagation. Therefore, the credit event of a single entity spread risk across the whole network of institutions. This contagion effect has been demonstrated dramatically in the ongoing economic and financial crisis.We apply to the field of finance a -to our knowledge -novel way of measuring, quantifying and modelling the degree of systemic risk and the magnitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Most closely related to our article are the recent works by Meine et al (2015b); Christoffersen et al (2014); Koziol et al (2015) and Keiler and Eder (2013). The paper by Meine et al (2015b) provides evidence that the propensity of a bank to experience extreme co-movements in its own credit default swap together with the market is priced in the CDS during the financial crisis.…”
Section: Determinants Of Cdssupporting
confidence: 57%
See 1 more Smart Citation
“…Most closely related to our article are the recent works by Meine et al (2015b); Christoffersen et al (2014); Koziol et al (2015) and Keiler and Eder (2013). The paper by Meine et al (2015b) provides evidence that the propensity of a bank to experience extreme co-movements in its own credit default swap together with the market is priced in the CDS during the financial crisis.…”
Section: Determinants Of Cdssupporting
confidence: 57%
“…However, their study is limited to a sample of banks and their model is restricted to the skewed t-copula, while our paper studies the effect of different copulas and we do not restrict our study to a sample of banks. Going in the same direction is the study of Keiler and Eder (2013). They address the question of how the CDS spread of one financial company is influenced by the CDS spreads of other financial companies within the system.…”
Section: Determinants Of Cdsmentioning
confidence: 99%
“…However, the existing academic literature has already demonstrated that other factors, having a more systematic nature, such as general economic conditions but also liquidity, plays a role. Recently, Giglio (2011) or Keiler and Eder (2013) further suggest the importance of a systemic factor.…”
Section: Price Discovery Processmentioning
confidence: 98%
“…Similarly, Berndt et al (2005) suggest that CDS spreads are likely not attributed to credit risk alone and Annaert et al (2013) notably conclude that liquidity and global economic variables are important to explain CDS variations. More recently, Keiler and Eder (2013) investigate the degree of systemic risk and the importance of potential spill-over effects in the banking system by analyzing the determinants of CDS spreads using spatial econometric approach. Such technique enables them to look at the existing cross-sectional interactions and to distinguish between three main components: a systemic one, a systematic one and an idiosyncratic one.…”
Section: The Determinants Of Credit and Cds Spreadsmentioning
confidence: 99%
See 1 more Smart Citation